THE PRACTICES OF USING RESULTS OF NATIONAL UNIVERSITY RANKINGS BY RUSSIAN UNIVERSITIES - Yu. V. Semenova (Moscow Polytechnic University, 2017)
The article focuses on using the results of national university rankings by Russian universities. The author identifies the practice of the ranking results transfer to potential stakeholders, the key groups of stakeholders for universities and the main tools of result transfer. The paper high-lights using of ranking results by the universities as data for analytics, benchmarking and indicative planning. The author dwells on some practices of using ranking results for development strategies elaboration and the positions responsible for working with the ratings. In conclusion several recommendations are given to expand the potential for working with university rankings.